Drukte, werk, liefde : loopbaan en gezin in het leven van universitair gediplomeerde veertigers - Elchardus, Mark; Huysseune, Michel (Brussel : VUBpress, 2000)
BMLIK
Nederlands
Monografie
Keywords: gezinnen